2014
DOI: 10.1007/s10098-014-0760-5
|View full text |Cite
|
Sign up to set email alerts
|

New proposal for production of bioactive compounds by supercritical technology integrated to a sugarcane biorefinery

Abstract: An integrated biorefinery is designed for the production of a broad range of products (e.g., bioactive compounds, biofuel, heat and bioelectricity) via multiple conversion pathways and technologies, being supercritical technology applied for the recovery of bioactive compounds from natural sources. In this study, first the effects of the extraction conditions from Brazilian ginseng (Pfaffia glomerata) roots including pressure (10-20 MPa), temperature (323-363 K) and CO2/ethanol proportion ratio (90:10 %, 50:50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The economic benefit of placing an SFE process inside a sugarcane biorefinery was stated previously by Santos et al [8], considering Brazilian ginseng roots as model vegetable biomass. Placing one biorefinery next to other can lead to shared waste and water treatment, shared utility production, use process wastes as raw-material in new processes and other benefits depending on the type of biomass and/or biorefinery studied.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The economic benefit of placing an SFE process inside a sugarcane biorefinery was stated previously by Santos et al [8], considering Brazilian ginseng roots as model vegetable biomass. Placing one biorefinery next to other can lead to shared waste and water treatment, shared utility production, use process wastes as raw-material in new processes and other benefits depending on the type of biomass and/or biorefinery studied.…”
Section: Resultsmentioning
confidence: 87%
“…The sugarcane biorefinery here considered employed the conventional ethanol production the technologies available in modern ethanol distilleries in Brazil and also produced second generation ethanol though enzymatic hydrolysis as described elsewhere [1,8,10]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supercritical fluid extraction (SFE) has demonstrated to be an ideal clean technology to be used as part of a holistic biorefinery for the recovery of bioactive compounds from plants and other vegetal materials, prior to its chemical conversion, indicating that SFE can be effectively used during the firststep in biorefinery concepts [13]. Additionally, the benefits of constructing a SFE plant in close proximity to an alcoholic fermentation facility that produces high purity CO 2 as a by-product and ethanol, was already recently demonstrated by our research group [14,15], thus this paper aims to contribute to analyze the impact of some ideas of different researchers to guide future investigation towards the more promising direction.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, other important compounds have been identified and could be also recovered with a subsequent extraction process. Our research group has demonstrated that pressurized ethanol, with or without the addition of CO 2 , can successfully be applied as solvent for extracting selectively β-ecdysone from P. glomerata roots (Leal et al, 2010;Santos et al, 2014). On the other hand, a recent patent developed by us described that water can be used as extracting solvent for obtaining a saponin-rich extract that can be used directly as surfactant (Meireles et al, 2013).…”
Section: Introductionmentioning
confidence: 99%